Mengintegrasikan Model Keberhasilan Proyek Sistem Informasi dan Pengalaman Pengguna untuk Menilai Penggunaan Sistem Informasi - Dwi Yuniarto (STMIK Sumedang, 2020)
Research on measuring User Experience on the use of information systems has contributed to decision making in several organizations, it's just that nothing is integrated with the success of its use. This study produces a model that can be used as an alternative model to measure the successful use of information systems by combining two models, namely Lee's User Experience model with McLean's and DeLone's Information System Project Success. The integration of these two models is assisted by the Input-Process-Output logic and the processional development model and the causal model and consists of seven variables and twenty-three indicators. The existence of this hybrid model is expected to help organizations to measure project success based on User Experience in the use of information systems.